A Theoretical Framework for Risk Analyses of Working from home: The FTSE 100 Employer’s Perspective. - Sharma, Saurav (2022)
This paper identifies existing literature on the societal phenomenon of working from home, a behavioural norm catalysed by the COVID-19 pandemic. This paper uniquely expands the academia and practical application capabilities of this societal risk using the perspective of FTSE 100 Index employers. This employer perspective has been applied throughout this paper using the globally recognised and accredited risk management process. This process is used to map out the risk appetite, identification, measurement and treatment of respective macroenvironmental risks a FTSE 100 firm may face in line with Government policies, organisational protocols, objectives and external regulations. To holistically and accurately target and control these work-from- home risks, this paper uses industry-recognised frameworks, scales and matrices to analyse and illustrate the actions and measures FTSE 100 firms can implement. To conclude, this paper makes three critical recommendations a FTSE 100 firm can consider based on the analyses conducted in this research paper: a new work-from-home policy that outlines a new hybrid working structure; the conduction of a quantitative study to help FTSE 100 firms with the effective long-term management of office spaces; and thirdly a groundbreaking investment in technology infrastructure to effectively and compliantly monitor employees working from home. Further to these findings, it is worth noting the results from this paper can be reconfigured over time as the societal and market conditions a FTSE 100 firm faces may be subject to change.